2012
DOI: 10.1089/tmj.2011.0108
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Electrocardiogram Images Sent Through the Mobile Phone Multimedia Messaging Service

Abstract: Our findings suggest that sending the ECG images via a multimedia message service may be a practical and inexpensive telecardiology procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…One trial reported better performance in a cardiac arrest simulation for health care providers allocated to receiving a mobile phone application regarding advanced life support [67]. One trial reported more errors in interpreting ECGs delivered by MMS compared to paper print-outs [68].…”
Section: Discussionmentioning
confidence: 99%
“…One trial reported better performance in a cardiac arrest simulation for health care providers allocated to receiving a mobile phone application regarding advanced life support [67]. One trial reported more errors in interpreting ECGs delivered by MMS compared to paper print-outs [68].…”
Section: Discussionmentioning
confidence: 99%
“…Emergency physicians interpreted all EKGs, and interpretation may have varied when compared to cardiologists or internists, although prior work suggests inter-specialty interpretation of EKGs may be similar. 17 The errors in interpretation of the texted images compared to the original EKC may be a concern. However, they may be no more than natural intra-observer variation, and the disagreements may be not be related to the quality of the texted images.…”
Section: Discussionmentioning
confidence: 99%
“…16 No presente estudo, os resultados obtidos mostram uma concordância considerável entre as análises dos ECGs originais e dos foto-ECGs adquiridos pela câmera digital (72%) ou do celular (74%). Resultados ainda mais expressivos foram encontrados na pesquisa de Bilgi et al, 16 onde foi analisada a acurácia na interpretação de 305 ECGs obtidos em uma emergência, fotografados por um celular e enviados por sistema de mensagem multimídia ao celular de um cardiologista remoto.…”
Section: Discussionunclassified